Coucou c'est encore moi, maintenant il me faut simplifier des expressions
besoin d'aide !!!
A= (8x +5) - (6x + 2)
B= (7x -3) - (3x -2)
C= (9x -6) + (-4x +7)
D= - 4x - (3x² -2x +8)
E= 8x - (3x + 5) X 2
F= (8x + 9) - (-3x + 4)
G= (-3x + 7) - (8x -2)
H= (8x -2) + (6x +4)
I = 6x² - (4x² -3x + 5)
J= 5x - (8x + 6) X3
merci

1

Réponses

2014-03-07T16:56:27+01:00
A= (8x +5) - (6x + 2) = 8x +5 -6x -2 = 2x +3
B= (7x -3) - (3x -2) = 7x -3 -3x +2 = 4x -1
C= (9x -6) + (-4x +7) = 9x -6 -4x +7 = 5x +1
D= - 4x - (3x² -2x +8) = 4x -3x² +2x -8 = -3x² +6x -8
E= 8x - (3x + 5) X 2 = 8x - 6x +10 = 2x +10
F= (8x + 9) - (-3x + 4) = 8x +9 +3x -4 = 11x +5
G= (-3x + 7) - (8x -2) = -3x +7 -8x +2 = -11x +9
H= (8x -2) + (6x +4) = 8x -2 +6x +4 = 14x +2
I = 6x² - (4x² -3x + 5) = 6x² -4x² +3x -5 = 2x² +3x -5
J= 5x - (8x + 6) X3 = 5x - 24x -18 =  - 19x -18
merci